Anti-Influenza Prodrug Oseltamivir Is Activated by Carboxylesterase Human Carboxylesterase 1, and the Activation Is Inhibited by Antiplatelet Agent Clopidogrel - Shi, Deshi; Yang, Jian; Yang, Dongfang; LeCluyse, Edward L.; Black, Chris; You, Li; Akhlaghi, Fatemeh; Yan, Bingfang (The Journal of pharmacology and experimental therapeutics, 2006)
Oseltamivir is the main medicine recommended by the World Health Organization in anticipation of next influenza pandemic. This anti-influenza viral agent is an ester prodrug, and the antiviral activity is achieved by its hydrolytic metabolite: oseltamivir carboxylate. In this study, we report that the hydrolytic activation is catalyzed by carboxylesterase human carboxylesterase (HCE) 1. Liver microsomes rapidly hydrolyzed oseltamivir, but no hydrolysis was detected with intestinal microsomes or plasma. The overall rate of the hydrolysis varied among individual liver samples and was correlated well with the level of HCE1. Recombinant HCE1 but not HCE2 hydrolyzed this prodrug and produced similar kinetic parameters as the liver microsomes. Several HCE1 natural variants differed from the wild-type enzyme on the hydrolysis of oseltamivir. In the presence of antiplatelet agent clopidogrel, the hydrolysis of oseltamivir was inhibited by as much as 90% when the equal concentration was assayed. Given the fact that hydrolysis of oseltamivir is required for its therapeutic activity, concurrent use of both drugs would inhibit the activation of oseltamivir, thus making this antiviral agent therapeutically inactive. This is epidemiologically of significance because people who receive oseltamivir and clopidogrel simultaneously may maintain susceptibility to influenza infection or a source of spreading influenza virus if already infected.